Control of the AC Induction Motor by Using Fuzzy Logic - Abdullah, Aws M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The main aim of this research to study and recognize the specifications and main concepts of (Fuzzy Logic) and its components and studying the practical experiments of the (Fuzzy Logic) techniques in the electrical engineering field through by using the (Fuzzy Logic) for controlling the three-phase AC induction motor by using (Matlab_ simulation_7) for modeling the system by using the computer